1996
DOI: 10.1088/0022-3727/29/11/004
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxides as a hole-injecting layer for an organic electroluminescent device

Abstract: We demonstrate that by using thin films of metal oxides, such as vanadium oxide (VOx), molybdenum oxide (MoOx) and ruthenium oxide (RuOx), as a hole-injecting layer for an organic electroluminescent (EL) device consisting of N,N'-diphenyl-N,N-bis(3-methylphenyl1)1,1'-biphenyl-4,4' diamine (TPD) and tris-(8-quinolinolato) aluminium (Alq), the EL device performance can be significantly improved. The `operating voltage' of the device is reduced with respect to a device with a well known indium - tin-oxide (ITO) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
200
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(203 citation statements)
references
References 16 publications
1
200
2
Order By: Relevance
“…17,18 Specifically molybdenum trioxide ͑MoO 3 ͒ has proven to be an attractive material and has been used as a HIL in organic LEDs based on small molecules, [19][20][21][22] as buffer layer in organic solar cells 23,24 and as connecting layer in tandem organic LEDs. 25 The working mechanism of MoO 3 as HIL is generally ascribed to the formation of an interfacial dipole and consequently a reduction of the injection barrier.…”
mentioning
confidence: 99%
“…17,18 Specifically molybdenum trioxide ͑MoO 3 ͒ has proven to be an attractive material and has been used as a HIL in organic LEDs based on small molecules, [19][20][21][22] as buffer layer in organic solar cells 23,24 and as connecting layer in tandem organic LEDs. 25 The working mechanism of MoO 3 as HIL is generally ascribed to the formation of an interfacial dipole and consequently a reduction of the injection barrier.…”
mentioning
confidence: 99%
“…The ITO coated glass was thoroughly cleaned using the process of scrubbing, ultrasonication, and irradiation in an UV-ozone chamber. Firstly, molybdenum trioxide (MoO 3 ) [16][17][18] as an effective hole injection layer was deposited on ITO substrate. Absorption spectra of evaporated thin film materials were measured using a fiber optical spectrometer (Ocean Optics, S2000) and deuterium/tungsten lamps (Hamamatsu Photonics, L10671).…”
Section: Methodsmentioning
confidence: 99%
“…As acceptors, organic dopants such as F 4 -TCNQ [30,31] and inorganic dopants like MoO 3 , V 2 O 5 , etc. [32,33] were found. In terms of donors that are relatively stable in air, Harada et al found a Ru-complex and applied it to fabricate pn-homojunctions in zinc phthalocyanine [34,35] and pentacene [36].…”
Section: Introductionmentioning
confidence: 97%